Penggunaan aplikasi gmeet untuk work from home di era pandemi covid-19: The use of gmeet application for work from home in the covid-19 pandemic era - Mariskha Z; Yulia Pebrianti; Esya Alhadi; Fetty Maretha (IGKOJEI: Jurnal Pengabdian Masyarakat, 2022)
ABSTRACT  The objective of this service activity was to train lecturers in Business Administration Department to use Google Meet application in order to facilitate long distance or online learning activities in this pandemic. The implementation methods were done by tutorials, demonstrations and questions and answers. Before the activities were carried out, the organizing team provided a list of questions about the application. It was found that 26% participants had not yet mastered the application, 28.67% less mastered the application, 13% had sufficiently mastered the application, and 32% was very good at the application. Then, the activities were continued to training activity or tutorials, and after the activities are completed, the participants were given a list of questions regarding the use of the application. The results obtained after the activity were 6% participants had not mastered the application, 15% less mastered the application, 33% had sufficiently mastered the application, and 46% were very good at the application. Thus, this service activity could help provide an understanding to the participants about the use of Google Meet application and all of features available in the Google Meet application.  Keywords: Application, Meet Google, Training   ABSTRAK  Tujuan dari kegiatan pengabdian ini adalah untuk melatih dosen pada jurusan Administrasi Bisnis dalam penggunaan aplikasi Google Meet dalam rangka mempermudah kegiatan belajar jarak jauh atau daring. Metode pelaksanaan yang dilakukan yaitu dengan cara tutorial, demonstrasi dan tanya jawab. Sebelum kegiatan dilakukan tim pelaksana memberikan daftar pertanyaan mengenai aplikasi didapatkan 26% belum menguasai aplikasi, 28,67% kurang menguasai aplikasi, 13% cukup menguasai aplikasi, dan 32% sangat menguasai aplikasi. Kemudian dilanjutkan dengan kegiatan pelatihan atau tutorial, dan setelah kegiatan selesai peserta diberikan kembali daftar pertanyaan mengenai penggunaan aplikasi. Hasil yang didapatkan setelah kegiatan yaitu peserta yang belum menguasai aplikasi sebesar 6%, kurang menguasai aplikasi sebesar 15% cukup menguasai aplikasi sebesar 33% dan 46% sangat menguasai aplikasi. Dengan demikian kegiatan pengabdian ini dapat membantu memberikan pemahaman kepada para peserta mengenai penggunaan aplikasi google meet dan pemahaman tentang semua fitur yang ada pada aplikasi google meet. Kata kunci: Aplikasi, Google meet, Pelatihan